Maryam's Sacrifice In The Outcast Novel By Okky Madasari (2014): An Individual Psychological Approach - KURNIASARI, DYAH HAYU; , Dr. Phil. Dewi Candra, M.Ed; , Siti Fatimah, S,Pd., M.Hum (2015)
This research paper aims at knowing the sacrificeof Maryam reflected in The Outcast novel by OkkyMadasari which is analyzed by using individual psychological. The objective of the research is to analyze the novel based on the structural elements of the novel and to analyze the novel based on individual psychological proposed by Alfred Adler. The type of this research is descriptive qualitative. Data of the research are taken from primary and secondary data. The primary data of the research is The Outcast novel. The secondary data of the research are taken from books, other source and website that related to the study. The technique of collecting data are reading novel, classifying the data, identifying the data that can be analyzed, taking note, and browsing to the internet. The method to analyze of this data is descriptive analysis. Based on structural elements of the novel, the Writer delivers a moral message that "Sacrifice for love, justice and faith as minority in society". Based on the individual psychological analysis, the author illustrates a psychological phenomenon which an individual should make every effort to cope with the problem of life. The psychological phenomenon is shown by the sacrifice of Maryam to get her right and protect from government. Maryam uses her creativity to manage her mind. She also arranges her striving for superiority to provide her inferiority feeling to create fictional finalism. Keywords: Sacrifice, Individual Psychological Approach, The Outcast novel